2018
DOI: 10.1039/c8ra03792b
|View full text |Cite
|
Sign up to set email alerts
|

Diketopyrrolopyrrole-based acceptors with multi-arms for organic solar cells

Abstract: Three small molecules SBF-1DPPDCV, SBF-2DPPDCV and SBF-4DPPDCV consisting of a spirobifluorene (SBF) unit as the core and one, two, and four diketopyrrolopyrrole dicyanovinyl (DPPDCV) units as the arms have been designed and synthesized for solution-processed bulk-heterojunction (BHJ) solar cells. The UVVis absorption and cyclic voltammetry measurement of these compounds showed that all these compounds have an intense absorption band over 300-750 nm with a LUMO energy level at around À3.87 eV. When pairing wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It was further confirmed that the cesium carbonate layer could passivate surface defects of the quantum dot layer to improve radiation recombination and device efficiency. According to the curve in Figure.S9, the mobility of the QD film with cesium carbonate is 2.67× 10 8 , and that of the QD film without cesium carbonate is 3.07× 10 8 . It shows that the Cs 2 CO 3 has little effect on the mobility.…”
Section: Resultsmentioning
confidence: 94%
“…It was further confirmed that the cesium carbonate layer could passivate surface defects of the quantum dot layer to improve radiation recombination and device efficiency. According to the curve in Figure.S9, the mobility of the QD film with cesium carbonate is 2.67× 10 8 , and that of the QD film without cesium carbonate is 3.07× 10 8 . It shows that the Cs 2 CO 3 has little effect on the mobility.…”
Section: Resultsmentioning
confidence: 94%
“…Since the discovery of diketopyrrolopyrrole (DPP) in 1974 by Farnum et al, it has become one of the most widely used prototypical π-cores for organic electronic devices and high-performance pigments. The unique optoelectrical properties and good thermo- and photostability of DPP-based compounds have resulted in their extensive utilization in organic semiconductive materials , and fluorescent probes. , For example, several applications of DPP-containing compounds in the area of organic field effect transistors (OFETs), organic photovoltaics (OPVs), organic light-emitting diodes (OLEDs) and dye-sensitized solar cells (DSSC) have been reported. Our group is also interested in DPP-containing polymers as ambipolar materials for application in organic electronic devices .…”
mentioning
confidence: 99%